2021
DOI: 10.9734/acri/2021/v21i830260
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and Safety: Africans Perspectives A Review

Abstract: The challenges of hunger in Africa, caused by food insecurity can only be mitigated by enhanced food security and food safety measures. Food safety has a significant role in ensuring food security. A primary cause of food insecurity is the decline in global food productivity. It is also a problem of poverty which has impacted adversely on the socio-economic life of its citizens. Africa is endowed with land resource that if transformed towards agricultural productivity has the capacity to ensure food security a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…According to research conducted by Harvard University Professor Calestous Juma, Africa could achieve food self-sufficiency if it stopped depending on food imports [ 9 ]. Farsund, Daugbjerg, and Langhelle [ 38 ] concluded that Africa’s land resource could quickly produce an additional 100 million tons of grain-equivalent a year if it were intensively farmed.…”
Section: The Sub-saharan African Food Security Situationmentioning
confidence: 99%
See 4 more Smart Citations
“…According to research conducted by Harvard University Professor Calestous Juma, Africa could achieve food self-sufficiency if it stopped depending on food imports [ 9 ]. Farsund, Daugbjerg, and Langhelle [ 38 ] concluded that Africa’s land resource could quickly produce an additional 100 million tons of grain-equivalent a year if it were intensively farmed.…”
Section: The Sub-saharan African Food Security Situationmentioning
confidence: 99%
“…The World Bank estimated in 2000 that 85–90% of agriculture in Sub-Saharan Africa relied on rainwater for survival and that agriculture accounted for 35% of the region’s GDP, 40% of exports, and 70% of its employment [ 9 ]. Agricultural output may not be sustainable with an annual rainfall of less than 700 mm.…”
Section: Why Is Sub-saharan Africa the Worst In Terms Of Food Insecur...mentioning
confidence: 99%
See 3 more Smart Citations